The reform and modernization of vocational education and training in China - Yan Hao (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
Vocational education and training (VET) is defined in general practice as technical education and skills training mainly for jobs that are based on manual or practical activities. According to China's 1996 Vocational Education Law, VET is deemed a key component of China's educational system, and an important means to promote employment, economic growth and social advancement. The Chinese government has attached great importance to VET since the founding of the People's Republic in 1949. The 1996 Vocational Education Law and the State Council's 2002 Decision on Vigorously Promoting the Reform and Development of VET represents the government's renewed effort at supporting VET in the era of reform and open-up. In recent years, additional reform measures have been introduced to modernize the existing VET system in line with the readjustment of China's development strategy and industrial structure.
Keywords: 330